Positive Aspekte von Erosionsprozessen - Haffner, Willibald; Justus Liebig University Giessen (My University, 1995)
Negative Aspekte von Erosion, insbesondere der Bodenerosion, sind in der Fachliteratur vielseitig dokumentiert. Dieser Aufsatz geht der Frage nach, welche positiven Aspekte erosiven Sediment- und Bodenverlagerungen abzugewinnen sind. Folgende Beispiele aus Mitteleuropa, Nepal und dem Jemen werden diskutiert:- Entstehung edaphischer Gunsträume durch Wasser- und Winderosion- Bodenabtrag im Muschelkalk: Auf- oder Abwertung des erodierten Standortes?- Erschließung kalk- und nährstoffreicher Lößhorizonte durch Bodenerosion- Erosionsprozesse und ihre Bedeutung für tropische Gebirgsböden- Anthropogene erosive Bodenverlagerung und Entstehung von Ackerkolluvien im Terrassenfeldbau- Zufuhr von gelöstem und suspendierten Erosionsmaterial im Naßreisbau

The negative aspects of erosion, especially of soil erosion are well documented from around the world. In contrast, this paper suggests that we can describe erosion in a more positive way, at least in some special cases. The following examples to underline this thesis are discussed in the paper:- Fertile alluvial plains and loess areas initiated by water and wind erosion;- Soil erosion on lime-stone slopes, amelioration or deterioration?- The opening of subsurface loess layers rich in lime and plant nutrients by soil erosion;- Tropical mountain soils: the input of relatively unweathered sediment matter in the top soil layers by erosion;- Man induced soil erosion and the accumulation of fertile colluvial sediments in combination with rain water collecting areas;- The input of dissolved and suspended matter by irrigation water in wet rice cultivation.
Positive aspects of erosion
Keywords: ddc:550